2002
DOI: 10.1002/cncr.10987
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of DFF45/ICAD is correlated with a poor prognosis in patients with esophageal carcinoma

Abstract: The dynamics of the stirred tank reactor polymer electrolyte membrane (STR‐PEM) fuel cell arise from the balance between water production and water removal within the cell. This results in STR‐PEM fuel cell steady‐state multiplicity, remarkably analogous to that of an autocatalytic exothermic STR. Model flooding effects in the cathodeside catalyst/gas diffusion layer by accounting for relevant mass‐transport processes is presented. We use the resulting STR‐PEM fuel cell model as a building block to construct a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 95 publications
2
34
1
Order By: Relevance
“…In esophageal cancer, prognostic markers such as E-cadherin, MDM2 and HGF have been reported (21)(22)(23). We previously showed that expression of DNA fragmentation factor 45, excision repair cross complementing 3, and PABPC1 may be prognostic markers for ESCC (24)(25)(26). Girdin may now be added to this list.…”
Section: Discussionmentioning
confidence: 98%
“…In esophageal cancer, prognostic markers such as E-cadherin, MDM2 and HGF have been reported (21)(22)(23). We previously showed that expression of DNA fragmentation factor 45, excision repair cross complementing 3, and PABPC1 may be prognostic markers for ESCC (24)(25)(26). Girdin may now be added to this list.…”
Section: Discussionmentioning
confidence: 98%
“…Recent molecular biological studies have revealed that ESCC is caused by the accumulation of multiple genetic defects in dominant oncogenes and tumor suppressors. We have also reported the expression of surviving (1), DFF45/ICAD (2), PTTG (3), Chfr (4), PPARγ (5), ERCC3 (6), PABPC1 (7) and ACP6 (8) to significantly correlate with the tumor progression and prognosis in patients with ESCC.…”
Section: Introductionmentioning
confidence: 84%
“…Decreased DFF45 expression is shown to associate with higher-stage neuroblastoma (Abel et al, 2002) and a poorer prognosis in some cancer patients (Konishi et al, 2002). DFF40/45 is also a candidate tumor suppressor for neuroblastomas.…”
Section: Introductionmentioning
confidence: 99%